The fate of the balanced scorecard: alternative problematization and competing networks - Gooneratne, T.N.; Hoque, Z. (Emerald Publishing, 2021)
Purpose – This paper aims to report on an empirical investigation of the fate of the balanced scorecard (BSC) approach in an organization. Design/methodology/approach – Building on actor-network theory and using a qualitative case study approach, this study analyses how across time certain actors attempted to build a competing network in the organization to gain support for their underlying rationales for replacing the BSC with a budgeting system. Data were collected using interviews, observations and archival data from a Sri Lankan commercial bank. Findings – This paper finds that despite the enthusiastic journey with all its potentials to be a sustainable accounting innovation, the attraction towards the BSC innovation by the organization appeared to be temporary because the BSC knowledge claims that were advanced by its promoters had not been widely accepted by those involved in the practice. Such a consequence of innovation diffusion appeared to be the result of the failure of the innovation promoters in coordinating the heterogeneous interests of various actors involved in the practice. This study concludes that the BSC failed to be sustained, amid varying ideologies and interests of powerful actors across time and opponent actors’ perceived deficiencies in its adapted design attributes. Research limitations/implications – Although the findings relate to a Sri Lankan case, they offer important insight into how parallel, competing networks advocating different control systems may exist in an organization, and that the sustainability of a specific system may depend upon the efforts and the relative power of the advocators of that system. Practical implications – This paper sheds useful insights for practitioners on the effective implementation of accounting innovations and managing management control systems in organizations amid tensions associated with competing networks. Originality/value – The outcomes enhance the knowledge of how multiple networks operating in an organization could compete with one another, with the result that one network may fall apart while another network gains prominence in the corporate landscape across time, amid varying interests of key actors, their actions and interessement devices used
Keywords: Balanced scorecard; Actor-network theory; Budgeting; Competing networks